Multi-objective optimization and decision visualization of batch stirred tank reactor based on spherical catalyst particles - Žilinskas, Antanas; Baronas, Romas; Litvinas, Linas; Petkevičius, Linas (Nonlinear Analysis: Modelling and Control, 2019)
This paper presents a Bayesian approach rooted algorithm oriented to the properties of multi-objective optimization problems. The performance of the developed algorithm is compared with several other multi-objective optimization algorithms. The approach is applied to the multiobjective optimization of a batch stirred tank reactor based on spherical catalyst microreactors. The microbioreactors are computationally modeled by a two-compartment model based on reaction–diffusion equations containing a nonlinear term related to the Michaelis–Menten enzyme kinetics. A two-stage visualization procedure based on the multi-dimensional scaling is proposed and applied for the visualization of trade-off solutions and for the selection of favorable configurations of the bioreactor.
Keywords: multi-objective optimization; multi-dimensional scaling; microreactor; reaction– diffusion